How do chemical epistemological beliefs affect Chinese students' chemistry disciplinary competence? A structural equation modeling analysis - Zhu, Xiujin; Huang, Yanning; Liu, Hailiang (Frontiers in Psychology, 2025)
The shift in focus from knowledge dissemination to the cultivation of disciplinary competence has become a pivotal topic in K-12 science education reform. Scientific epistemological beliefs play a crucial role in students' learning processes and overall development. Although chemistry represents a vital component of science, little is known about how chemical epistemological beliefs affect students' chemistry disciplinary competence. This study aimed to explore the mechanisms by which epistemological beliefs influence students' chemistry disciplinary competence and to provide suggestions for fostering it. A sample of 182 11th-grade students participated in the formal evaluation. The results showed that (1) among the four dimensions of chemical epistemological beliefs—Source, Certainty, Justification, and Simplicity—the source and certainty beliefs substantially influenced chemistry disciplinary competence; (2) critical thinking disposition and chemistry learning approaches played separate mediating role in the influence of chemical epistemological beliefs on competence, and (3) the chain mediating effects of chemical epistemological beliefs, critical thinking disposition, chemistry learning approaches, and chemistry disciplinary competence were also significant. Findings suggest that developing chemistry disciplinary competence requires fostering sophisticated chemical epistemological beliefs to cultivate critical thinking disposition and deep learning approaches.